PENGARUH BAHAN AJAR DIGITAL INTERAKTIF TERHADAP KEMAMPUAN LITERASI SAINS SISWA KELAS IV SDN Dr SOETOMO 5 - Nashihah, Durrotun; Achmad Fanani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study has a background of learning problems of students of SDN Dr. Soetomo who have not been optimal in carrying out literacy. This study aims to determine the Effect of Interactive Digital Teaching Materials on the Scientific Literacy Skills of Fourth Grade Students of SDN Dr. Soetomo 5. The method used in this study is an experimental method, namely to determine the ability of fourth grade students in carrying out scientific literacy, this study is included in the form of a two-group daily test-posttest design study . The population in this study were all students of class 4A totaling 25 people and class 4C totaling 25 people. The sample of this study was students of class 4A totaling 25 people and class 4C totaling 25 people who were divided into two groups, namely class 4A as the experimental group and class 4C as the control group. Data collection was carried out using observation, test, and measurement techniques as well as documentation. The instrument used was a posttest test with a t-test data analysis technique. The results of the analysis showed that the sig . values . (2-tailed) in the experimental group were 0.000, the sig. value. (2-tailed) in the control group is 0.000, so the sig . value (2-tailed) in the experimental group is <0.05, so Ho is rejected, which means there is an influence of interactive digital teaching materials on scientific literacy skills in the science subject in Elementary Schools. Based on the results of the analysis above, it can be concluded that interactive digital teaching materials have an influence on scientific literacy skills in the science subject in elementary schools.